Desain UI&UX Aplikasi Web Pemesanan Dekorasi Miss Eka Gallery Dengan Metode User-Centered Design - Muhammad Reza Fahlefi; Hermansyah; Heni Wulandari (CV. Hawari, 2025)
Miss Eka Gallery is a decoration service business for various events such as weddings and birthdays that currently still uses conventional ordering methods through direct communication or social media. This ordering method often results in delayed responses, misinformation, and difficulties in order management. Therefore, this study was conducted to design a website application with optimal UI (User Interface) and UX (User Experience) design so that customers can easily view the decoration catalog, place orders, and get confirmation in real-time. The method used in this study is User-Centered Design (UCD) with a design thinking approach consisting of five stages, namely empathize, define, ideate, prototype, and test. Data were obtained through observation and questionnaires to application users to understand their needs, complaints, and preferences. The design results show that the developed web application prototype can display the decoration catalog well, simplify the ordering process, and provide easy service confirmation to customers. Based on testing using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) on 14 respondents, it was found that most users still felt less helped, especially in the aspects of navigation and clarity of decoration information. Respondents also suggested adding features such as a chatbot, QRIS payment methods, and a photo gallery of on-site decorations. The results showed that interactive and user-friendly UI/UX design can increase customer satisfaction. Further research is recommended to develop these additional features to optimize the application and meet user expectations.